Strategi Pemanfaatan Aplikasi Desa Apps dalam Literasi Informasi Pertanian - Alia Bihrajihant Raya; Mesalia Kriska; Sri Peni Wastutiningsih; Melisa Umi Cahyaningtyas; Adrian Djitmau; Galuh Friska Cahyani (Institut Pertanian Bogor, 2018)
Information literacy is one part of community empowerment activities, especially in the information field. Information literacy is the ability to search, evaluate, and use information needed effectively. Basically information literacy is not a new ability or skill, but in the era of information disclosure, information literacy is a must-have skill requirement. The problems faced today, there is still an imbalance between the pace of information available and the level of agricultural information literacy at the farm level. The development of agricultural information through the internet has led to cyber extensions, information is available quickly and varied, but not all farmers are able to access and use it. The Faculty of Agriculture UGM has developed an application with the name DesaApps. DesaApps stands for Digital Extension Society for Agriculture Application which aims to be an application platform that provides agricultural counseling and develops a digital farming community. The existence of DesaApps can be useful for users of the application to provide information to one another, interact and transact in agriculture. The features in the DesaApps application consist of Frequently Asked Questions, Articles, Price Information, Farm Notes, Weather Information. Shop Information, Office Information, and Selling Items. Utilization of the features provided by Desa Apps provides an opportunity for farmers to obtain the information needed, as well as a means of improving the skills of managing information obtained. Therefore, the presence of Desa Apps empowers farmers to be independently informed. However, the performance of Desa Apps as one of the sources of information still needs to be improved. In order to be able to optimize the use of Village Apps, the utilization strategy is to improve application performance, promote and promote Village Apps, responsiveness of experts, and optimize the use of Desa Apps as a marketing place.